(untitled) (CIPEEX, 2025)
Introduction: Obesity is a global health problem that has increased significantly in recent years. Bariatric surgery emerges as a treatment alternative for individuals with morbid obesity. Alongside obesity, the prevalence of non-alcoholic fatty liver disease (NAFLD) has also risen, predisposing these individuals to cirrhosis and hepatocellular carcinoma. Currently, liver biopsy remains the gold standard for diagnosis; however, it is an invasive procedure with potential complications. Therefore, new non-invasive tests have been proposed to identify such changes, such as hepatic elastography, which allows the detection of liver fibrosis without invasive procedures. Objective: To identify the degree of hepatic fibrosis in severely obese patients indicated for bariatric surgery using hepatic elastography. Methodology: Seven clinical trials were extracted from PubMed, published between 2019 and 2024. Health Science Descriptors (DeCS) used were: “Bariatric Surgery,” “Elastography,” and “Obesity.” Inclusion criteria were original studies published in English. Results: Elastography proved effective in detecting fibrosis, showing no significant differences when compared with liver biopsy. Only one study failed to show diagnostic accuracy in patients with higher BMI values. Conclusion: Elastography can be used to identify liver fibrosis in this population; however, further studies are required to reinforce these findings.